2009
DOI: 10.1111/j.1600-0404.1994.tb02704.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative SPECT cisternography in normal pressure hydrocephalus

Abstract: Twenty‐one patients with normal pressure hydrocephalus (NPH), 8 patients with various brain diseases with an element of hydrocephalus, and 7 patients with miscellaneous dementia disorders were investigated with quantitative radionuclide cisternography (RC) using single photon emission computerized tomography (SPECT). The total intracranial counts as well as the counts in the lateral and third ventricles were measured. All 15 NPH patients accessible for postoperative examination were improved after shunt surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 30 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…However, clear evidence for this clearance is still lacking. In iNPH the CSF flow above the convexities is reduced and redirected into the ventricles and iNPH patients often present with a disproportionately enlarged subarachnoid-space [ 28 , 29 ]. These findings could hypothetically be in accordance with a disturbance of CSF/ISF exchange as the dilated paravascular spaces could impair CSF/ISF exchange.…”
Section: Discussionmentioning
confidence: 99%
“…However, clear evidence for this clearance is still lacking. In iNPH the CSF flow above the convexities is reduced and redirected into the ventricles and iNPH patients often present with a disproportionately enlarged subarachnoid-space [ 28 , 29 ]. These findings could hypothetically be in accordance with a disturbance of CSF/ISF exchange as the dilated paravascular spaces could impair CSF/ISF exchange.…”
Section: Discussionmentioning
confidence: 99%
“…In patients over 70 years of age, shunted previously or after meningitis, reduction of the size of the ventricular system should not be expected [ 40 , 41 ]. More reliable information on the patency of the ventriculostomy may be provided by phase-contrast cine MRI or isotope cisternography [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…56,116) They are mainly derived from studies of sNPH, although its diagnostic significance is of some doubt even in sNPH. 125) A study of iNPH reported improvement of symptoms in 55% of all cases with normal findings on RI cisternography.…”
Section: Cisternographymentioning
confidence: 99%